2018
DOI: 10.1186/s41687-018-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

PRO-based follow-up as a means of self-management support – an interpretive description of the patient perspective

Abstract: BackgroundThere is an increasing focus on the use of patient-reported outcome (PRO) measures to improve the quality and effectiveness of health care. PRO-based follow-up is a new model of service delivery, where the patient’s PRO measures are used as the very basis for outpatient follow-up.ObjectivesThis study aimed to explore how patients with epilepsy experience the use of PRO-based follow-up in three outpatient clinics in the Central Denmark Region. We also sought to explain how these experiences relate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 28 publications
8
57
0
3
Order By: Relevance
“…A qualitative study has documented a variation in patients' preferences for being active and taking responsibility in PRO-based follow-up, as some patients experienced a lack of confidence in their own capability to participate [46]. In addition, a study regarding the clinician perspective indicated that some clinicians had concerns regarding some patients' capability to participate in PRO-based follow-up, even though the patient had already been referred [43].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study has documented a variation in patients' preferences for being active and taking responsibility in PRO-based follow-up, as some patients experienced a lack of confidence in their own capability to participate [46]. In addition, a study regarding the clinician perspective indicated that some clinicians had concerns regarding some patients' capability to participate in PRO-based follow-up, even though the patient had already been referred [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PROs may facilitate patient-centred consultations by providing patients with an opportunity to communicate on topics they find important and that may otherwise not be addressed [19,20]. However, the use of PROs in the clinic is not able in itself to ensure patient involvement and patientcentred consultations [21,22]. If clinicians do not value PROs or consider patients' assessment of the situation and of their illness as important knowledge, then PROs are suggested not to make a difference to the dialogue [23].…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…For clinicians, the harms may include information overload, spending time on finding and reviewing PRO data and identifying problems without being able to use the data in the consultation or having access to appropriate interventions [30]. For patients, answering PRO measures without receiving any or only superficial response to the problems reported, can leave them with a feeling of being abandoned and alone, and may cause decreased motivation for filling in the PRO measures [21]. Therefore, the first step towards success is to devise implementation strategies, including training of clinicians in using PROs in a clinical context.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…In outpatient settings, PRO measures can be seen as a precursor of the upcoming consultation, legitimizing its relevance. Although PRO measures hold much potential, research shows that applying PRO measures in clinical practice does not automatically promote patient involvement and improve communication [21,22]. A number of barriers impeding the improvement of healthcare quality through PRO measures have been identified.…”
Section: Introductionmentioning
confidence: 99%